Optimization of permanent-magnet synchronous motor for electric vehicle applications - Zhu, Siti Sarah Binte Zhuraimi @ Sarah (Nanyang Technological University, 2023)
The urgent need to address climate change is driving the rapidly expanding Electric Vehicle (EV) market. In response to the United Nations' (UN) call for nations to reduce their environmental impact by reducing Greenhouse Gas (GHG) emissions, there has been a shift towards EV production in place of conventional Internal Combustion Engines (ICEs). However, ensuring that EVs maintain the same driving force and torque as ICEs remains a challenge in facilitating a seamless transition for the public. Therefore, significant importance lies in improving existing EV models, such as the Toyota Prius, in this context.